Polymyalgia Rheumatica: Recent Advances and Ongoing Questions - Vinall, Maria (MD Conference Express, 2012)
Polymyalgia rheumatica is the most common inflammatory rheumatic disease of the elderly; however, accurate diagnosis is difficult as symptoms often overlap with those of other rheumatic and inflammatory diseases. To date, the development of therapeutic approaches has been hindered by a lack of standardized classification criteria.